2020
DOI: 10.2147/copd.s237545
|View full text |Cite
|
Sign up to set email alerts
|

<p>CODEXS: A New Multidimensional Index to Better Predict Frequent COPD Exacerbators with Inclusion of Depression Score</p>

Abstract: Depression is reported in association with chronic obstructive pulmonary disease (COPD). However, to date, no multidimensional indices have taken depression into consideration to predict COPD patients' prognosis. This study aimed to determine whether a new multidimensional index named CODEXS, based on comorbidities, airflow obstruction, dyspnea, previous exacerbation and depression assessed by Self-Rating Depression Scale (SDS), could predict 1-year exacerbations. Methods: This was a prospective study, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
(40 reference statements)
1
18
0
1
Order By: Relevance
“…Therefore, it was very relevant to evaluate the effective comorbidity in this vulnerable group, which also requires interventions adapted to socioeconomic conditions, in that these variables can interact as mediators or moderators in anxiety and depression. In addition, considering that the presence of anxiety and depression as comorbidities in COPD contribute to a substantial burden of COPD-related morbidity by impairing QOL and reducing treatment adherence (Hanania & O'Donnell, 2019;Khdour et al, 2012;Miravitlles et al, 2017;Pooler & Beech, 2014;Yohannes et al, 2018) In particular, depression has been identified as an independent risk factor for frequent exacerbations (Deng et al, 2020). The results we obtained indicate that it is justified to identify people with the symptoms of anxiety and depression (particularly occurring simultaneously) to provide them with additional psychological and therapeutic support in order not to further exacerbate the disorder but to reduce and eliminate it.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was very relevant to evaluate the effective comorbidity in this vulnerable group, which also requires interventions adapted to socioeconomic conditions, in that these variables can interact as mediators or moderators in anxiety and depression. In addition, considering that the presence of anxiety and depression as comorbidities in COPD contribute to a substantial burden of COPD-related morbidity by impairing QOL and reducing treatment adherence (Hanania & O'Donnell, 2019;Khdour et al, 2012;Miravitlles et al, 2017;Pooler & Beech, 2014;Yohannes et al, 2018) In particular, depression has been identified as an independent risk factor for frequent exacerbations (Deng et al, 2020). The results we obtained indicate that it is justified to identify people with the symptoms of anxiety and depression (particularly occurring simultaneously) to provide them with additional psychological and therapeutic support in order not to further exacerbate the disorder but to reduce and eliminate it.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown to be useful at predicting survival and readmission after hospital discharge for a COPD exacerbation, with a prognostic capacity superior to other previously published indices. 11,12 Since COPD is related with an increased risk of cardiovascular events, especially in the more advanced phase of the disease and in patients with exacerbations, assessment of the overall cardiovascular risk in these patients seems essential, and similar therapeutic target levels for glycosylated hemoglobin, low-density lipoprotein cholesterol (LDL-C), blood pressure, dietary interventions and adapted physical activity recommended by clinical practice guidelines for patients at high cardiovascular risk should be achieved. 13 We aimed to describe salient findings of major cardiovascular comorbidities associated with COPD based on the current best evidence from the recent medical literature (published from 2015), which, on the other hand, will contribute to reinforce recommendations of a recent Spanish consensus on the management of COPD according to the CODEX index.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that the prevalence of depression in COPD is higher in frequent exacerbators and that depression is more severe in patients at a higher COPD stage. 12 In our population, patients with depression have a higher risk of readmission for AECOPD, regardless of lung function and severe exacerbations in the previous year, evaluated as attending the Emergency Department or being admitted to hospital. In a systematic review, Lecheler et al reported high readmission rates in patients with depression hospitalized for AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depression and anxiety interfere with other risk factors, such as tobacco use, and, in general, they impair patients' quality of lif. 3,11 However, the debate on the impact of anxiety and depression on the prognosis of COPD patients continues, as some authors report worse disease progression, [12][13][14] while other researchers have not observed any association between anxiety or depression and worse prognosis of acute exacerbations of COPD (AECOPD). 15,16 Also, though some studies have analyzed the relationship between depression and anxiety with COPD, both entities are underdiagnosed in these patients and therefore rarely treated properly.…”
Section: Introductionmentioning
confidence: 99%